1996
DOI: 10.1073/pnas.93.10.5166
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pharmacological properties and distribution in neurons and endocrine cells of two isoforms of the human vesicular monoamine transporter.

Abstract: A second isoform of the human vesicular monoamine transporter (hVMAT) has been cloned from a pheochromocytoma cDNA library. The contribution of the two transporter isoforms to monoamine storage in human neuroendocrine tissues was examined with isoform-specific polyclonal antibodies against hVMAT1 and hVMAT2. Central, peripheral, and enteric neurons express only VMAT2. VMAT1 is expressed exclusively in neuroendocrine, including chromaffin and enterochromaffin, cells. VMAT1 and VMAT2 are coexpressed in all chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
389
3
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(411 citation statements)
references
References 40 publications
17
389
3
2
Order By: Relevance
“…VMAT1 is preferentially expressed by adrenal chromaffin cells and by small intensely fluorescent cells in sympathetic ganglia (Weihe et al, 1994). By contrast, selective VMAT2 expression has been reported for noradrenergic sympathetic neurons, midbrain dopamine neurons and other monoaminergic neurons in the brain stem (Erickson et al, 1996;Weihe and Eiden, 2000;Weihe et al, 1994). Taken together, this earlier literature conveys the distinct impression that all noradrenergic sympathetic neurons are immunoreactive for VMAT2.…”
Section: Introductionmentioning
confidence: 68%
“…VMAT1 is preferentially expressed by adrenal chromaffin cells and by small intensely fluorescent cells in sympathetic ganglia (Weihe et al, 1994). By contrast, selective VMAT2 expression has been reported for noradrenergic sympathetic neurons, midbrain dopamine neurons and other monoaminergic neurons in the brain stem (Erickson et al, 1996;Weihe and Eiden, 2000;Weihe et al, 1994). Taken together, this earlier literature conveys the distinct impression that all noradrenergic sympathetic neurons are immunoreactive for VMAT2.…”
Section: Introductionmentioning
confidence: 68%
“…VMAT2 is a neuronally expressed subtype of the vesicular monoamine transporter responsible for loading synaptic vesicles with the monoamine neurotransmitters serotonin, norepinephrine, dopamine, and histamine (Liu et al, 1992;Peter et al, 1994;Erickson et al, 1992Erickson et al, , 1996. Mice lacking both copies of the VMAT2 gene die during development, but heterozygotes survive and show reduced amphetamineconditioned reward, enhanced amphetamine and cocaineinduced locomotion, and enhanced MPTP toxicity (Takahashi et al, 1997;Wang et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The reason why certain carcinoid tumours cannot be visualised has not been explained, and the precise mechanism behind MIBG uptake and retention in NE tumours is unclear. It has been shown that MIBG is a substrate for VMATs, located on the membrane of secretory vesicles of NE cells (Henry et al, 1994;Erickson et al, 1996). It is therefore likely that after passing the plasma membrane, MIBG is transported into secretory granules by VMATs.…”
Section: Discussionmentioning
confidence: 99%